LEGAL PROTECTION FOR ELECTRONIC EDITORS (World Bulletin of Management and Law, 2022)
In this study, we focused on the legal protection statement for electronic documents, and we discussed the concept of the electronic editor as electronic support for storing data and information so that it can be referenced when needed. The electronic document relies on a new type of writing, which is electronic writing, and if this writing determines a right, it has a legal value. The electronic editor has three parties: the originator of the electronic message (the sender), the recipient, and the mediator. Writing the electronic editor requires conditions, namely, the readability of the electronic editor, the preservation of the integrity of the data recorded in it, and the non-penetration of it so that no one can view it and not prejudice its contents except for those who have the encryption key. Types of encryption, are symmetric, asymmetric, double, and security for electronic transactions. The Iraqi electronic signature and electronic transactions law did not address the concept of the electronic editor and the subject of electronic encryption and its databases over the Internet. From seeing it manipulate it.